Methane gas sensing behavior of lithium ion doped carbon nanotubes sensor. (August 2018) - Chen, Xiaoyu; Huang, Zonghou; Li, Jia; Wu, Chunlei; Wang, Zhan; Cui, Yuming
Abstract: A sensor for detecting and estimating methane using lithium ion doped carbon nanotubes as the sensing element has been developed. The sensitivity of the sensor increases linearly with the methane content in the concentration range of 50–500 ppm and the maximum sensitivity is about 14.5% at 500 ppm. Characteristics such as repeatability, selectivity, stability of the sensor have been investigated. The results indicate the sensor exhibits good sensitivity and selectivity to methane, and is repeatable and stable. A reliable and convenient method of developing a methane gas sensor has been proposed. Highlights: The first attempt of introducing Li + into CNTs based gas sensor. This sensor has superb sensitivity, repeatability, selectivity and stability to CH4 even at room temperature. We propose a reliable and convenient method of developing a methane gas sensor.